X-ray Data and Transition Temperature Measurements of Ca Doped Bi2Sr2La2Cu3O10+Î´ Superconductor - Thejeel, M. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
We studied the effect of Ca- doping on the properties of Bi-based superconductors by adding differ ent amounts of CaO to the Bi2Sr2La2-xCaxCu3O10+Î´compound. consequently, we obtained three samples A,B and C with x=0.0, 0.4 and 0.8 respectively. The usual solid-state reaction method has been applied under optimum conditions. The x-ray diffraction analy sis showed that the samples A and B have tetragonal structures conversely the sample C has an orthorhombic structure. In addition XRD analysis show that decreasing the c-axis lattice constant and thus decreasing the ratio c/a for samples A,B and C resp ectively. The X-ray florescence proved that the compositions of samples A,B and C with the ratio of Bi:Sr :La(Ca):Cu which were about 2:2:2:3. Resistivity were measured at different temperatures under zero magnetic f ields and the data were interp reted. Sample A shows that semiconductor behavior, sa mple B showed a metal behavior andsa mple C showed a sup erconductor behaviors with transition temperatureat zeroresistanceTc( off set)were 85 K .